Development of Socrates-Based Mathematical Statistics Teaching Materials - Zubaidah Rasiman; Dona Fitriawan (Universitas Syiah Kuala, 2023)
The aims of this study are to: a) develop Socrates-based mathematical statistics teaching materials; b) testing the quality of teaching materials in terms of validity, effectiveness, and practicality. The research was carried out in the even semester of 2021/2022 in the fourth semester of the mathematical statistics course for all classes. This study uses a development method using a 4-D model consisting of 4 main stages, namely define, design, develop, disseminate. The product developed is in the form of teaching materials that have been tested for feasibility with content validity, effectiveness tests by analyzing student learning outcomes after the teaching materials are used and practicality tests through student response analysis. The collection techniques and instruments are: 1) indirect communication techniques with the instruments being expert validation questionnaires and response questionnaires for instrument validation and student responses; 2) the measurement technique with the instrument is a test of learning outcomes for the effectiveness of the product; 3) direct communication techniques with interview sheets as instruments to find out the advantages and disadvantages of teaching materials when used for students. The data analysis techniques are: a) describe or describe each step of development with a 4-D model; b) expert validation analysis on the feasibility of teaching materials, namely qualitative descriptive, the results of the study are stated in the form of logical analysis; c) calculation of the validity of the assessment results and validation of the consistency of the experts using Aiken's formulation. The overall research results are: 1) the development of Socrates-based mathematical statistics teaching materials is carried out according to the main 4-D stages in sequence; 2) Socrates-based mathematical statistics teaching materials have content validity and reliability with very high criteria; 3) student learning outcomes after using Socrates-based mathematics teaching materials are classified as high criteria. So it can be concluded that the teaching materials developed are effective.